POTRET IDEAL KEPEMIMPINAN PEREMPUAN SEBAGAI PENGELOLA LEMBAGA PAUD - Novan Ardy Wiyani (Yinyang: Jurnal Studi Islam Gender dan Anak, 2017)
This paper is intended to describe the ideal portrait ofwomen’s leadership in managing early childhood institutions. There areeight characteristics of the ideal figure of woman leaders, as follows:1) confident and having high idealism, 2) persistent and having ability tobuild a team work, 3) simple and humble, 4) wise in making a decision, 5)independent, 6) credible, 7) protecting, and 8) inspirational and can be amodel.